MEMBANGUN BUDAYA SEKOLAH MELALUI PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 3 PALU - Elya Elya (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study discusses how to build a school culture through the development of Islamic religious education in SMA Negeri 3 Palu. This study aims to develop and preserve the school culture (school culture) that is characterized and strong. The specific target achieved is how all school members can participate and apply religious culture, work team culture and leadership culture in interacting both in the classroom and outside the classroom with various programs that have been arranged by the school. The research method used is descriptive qualitative, data obtained through observations, interviews and documentation, location photos and behavior of all citizens of SMA Negeri 3 Palu. Data were analyzed with the Hubberman model which included data collection, data analysis, data verification and data reduction. The results showed that there were three components of school culture developed in SMA Negeri 3 Palu, namely: first, religious culture, namely culture instilling systematic behavior and manners in practicing their respective religions so as to form personalities and good attitudes (akhlaqul Karimah) and discipline in various matters, both in the classroom and outside the classroom. Second, the culture of team work is to instill a sense of togetherness and social sense through joint activities. Form of School Orientation (MOS) activities, industry visits, Parents Day, social service, foster friends, Sport and Art, Museum Visits, Performances of Art, Comparative Studies, Ekskul, Labs Channel, Labs TV, Labs Care, Student Release, School Uniforms, School Magazines, Potency Mapping. Third, the culture of leadership (Leadership), is to instill leadership and leadership from an early age. Form of Activity, Career Day; culture of hard work, smart and sincere, Creative culture; Independent and responsible, culture of discipline, cross-struggle student council, public lectures, flag ceremony, Friday Morning Sports, student leadership studies, LKMS, OSIS. With the motto agreed by the school for example being creative and achieving, it will make the school superior and quality. The implication of this research is that the school culture must remain strong and maintained, even the school is ready to share the experience of the achievements of the national high school achieved, to other schools in Central Sulawesi. Keywords: Building School Culture, Islamic Education